Nurses' intention to care for patients with infectious disease: a content analysis study - Esmaeil Hoseinzadeh; Abbas Ebadi; Tahereh Ashktorab; Hamid Sharif-Nia (BMC, 2023)
Abstract Objective This present study was designed to explain the concept of nurses intention to care of patients with infectious diseases. Methods This study is a deductive content analysis study that was performed from May 2022 to Jun 2022 in three hospitals in Iran. In total 21 nurses were chosen by purposive sampling and for deta collection used semi-structured interviews. Data analysis was done using Elo and Kingas method. Results This study have revealed the formation of seven distinct themes, namely Job satisfaction, Professional ethics, Personal values, Standard precautions, Preserving health, Support, and Attitude of patients and their families. These themes are comprised of 17 categories and 59 subcategories. Conclusion By comprehending the dimensions of nurses' intentions to care for patients with infectious diseases, it is possible to develop suitable planning and strategies to meet the healthcare requirements of such patients. Managers can take action by examining the issues and demands of nurses, and by providing job security, they can establish a Healthcare service systems with high security that can effectively respond during an outbreak of infectious diseases. Additionally, Nursing managers can prevent nurses from leaving their jobs by taking appropriate intervention, increasing their motivation, and enhancing their satisfaction.